MUSLIM STUDENTS’ PERCEPTION TOWARDS THE HALALNESS OF KOREAN FOOD CULTURE IN MALANG - Najia, Rifah (Universitas Islam Malang, 2023)
The development of the Korean Wave in Indonesia has proven to have a significant influence in various sectors, including the food sector. One of the problems that arise with the development in this sector is the concern of the Indonesian Muslim community about the halalness of Korean food itself, considering that Korea (in this case South Korea) is a country whose Muslim population is only 0.2% of the total population, so it is not surprising that many foods that come from there cannot be consumed by Muslims because they contain illegitimate compositions such as pork, lard, and alcohol. This research is a descriptive study using qualitative methods. The data was taken by means of structured online interviews through WhatsApp video calls involving 20 Muslim student participants with an age range of 18-23 years. This study aims to find out how the interest of Muslim students in Malang to taste Korean food and how cautious they are in choosing halal Korean food for their consumption